2018
DOI: 10.11648/j.ijbecs.20180402.11
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycaemic and Antihyperlipidemic Activities of <i>Pleiogynium timorense</i> Seeds and Identification of Bioactive Compounds

Abstract: The aim of this study is to evaluate antihyperglycaemi cand antihyperlipidemic activities of Pleiogynium timorense (DC.) Leenh (Anacardiaceae) seeds as well as to isolate and identify the bioactive compounds. Antihyperglycaemic effect was evaluated by measuring the effect of two dose levels (150 and 300 mg/kg) of 70% methanol extract of Pleiogynium timorense seeds on the blood glucose level. In addition, the effect of the plant extract on the lipid profile was determined by measuring serum total lipids (TL), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…These results confirmed that the seed extract is a rich source with the phytochemical constituents that contribute significantly in the plant bioactivities. This result was in agreement with what were reported by previous studies which found that flavonoids, terpenoids, saponins, carbohydrate, tannins and coumarins, were detected in the leaves, bark and fruits of P. timorense with absence of alkaloids 3,4, 10 . HPLC Analysis HPLC analysis of polyphenolic compounds revealed the identification of ten polyphenolic compounds in ethyl acetate extract of P. timorense seeds representing 87.2% of the total area, where chlorogenic acid (24.7 %), catechin (17.2%), Coumaric acid (7.4%), and gallic acid (7.3 %) represent the major compounds (Table 1 and Figure 1).…”
Section: Phytochemical Study Phytochemical Screeningsupporting
confidence: 93%
See 2 more Smart Citations
“…These results confirmed that the seed extract is a rich source with the phytochemical constituents that contribute significantly in the plant bioactivities. This result was in agreement with what were reported by previous studies which found that flavonoids, terpenoids, saponins, carbohydrate, tannins and coumarins, were detected in the leaves, bark and fruits of P. timorense with absence of alkaloids 3,4, 10 . HPLC Analysis HPLC analysis of polyphenolic compounds revealed the identification of ten polyphenolic compounds in ethyl acetate extract of P. timorense seeds representing 87.2% of the total area, where chlorogenic acid (24.7 %), catechin (17.2%), Coumaric acid (7.4%), and gallic acid (7.3 %) represent the major compounds (Table 1 and Figure 1).…”
Section: Phytochemical Study Phytochemical Screeningsupporting
confidence: 93%
“…IC 50 determination: Five concentrations were produced by serially dilution of extracts that exhibited an inhibition more than 50% in any of the concentrations used in the initial screening stage. Trolox stock solution: 100μM of trolox in methanol was prepared in various concentrations (5,10,15,20,30,40, and 50 μM).…”
Section: In Vitro Antioxidant Activity Sample Preparation Initial Scr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The seeds of the Burdekin plum have been shown to have antihyperglycaemica and antihyperlipidemic effects on rats by significantly reducing the levels of blood glucose, total cholesterol, total triglycerides, and low density lipoprotein cholesterol. The seeds contain the phenolic compounds catechin, gallic acid, paramethoxybenzaldehyde, and pyrogallol (104). The fruit have also shown a cytotoxic effect against breast adenocarcinoma and laryngeal carcinoma human tumor cells and a moderate cytotoxic effect on human hepatoma cells (105).…”
Section: Nutrition and Phytonutrients And Their Potential As Functionmentioning
confidence: 99%
“…Fifteen species of the Anacardiaceae family were selected to be reviewed for their pharmacological effects on controlling the lipid profile of dyslipidemia. Those species are Anacardium occidentale [17][18][19][20][21], Buchanania lanzan Spreng [22], Lennea edulis [23], Mangifera indica [24][25][26][27][28], Pistacia atlantica [29], Pistacia khinjuk [30], Pistacia lentiscus [31][32][33], Pleiogynium timorense [34], Protorhus longifolia [35], Rhus coriaria [36][37][38][39][40], Rhus mysurensis Heyne [41], Rhus verniciflua [42], Schinus terebinthifolius [43], Semecarpus anacardium [44,45], and Spondias pinnata [46,47]. As those species are varied, their substances are different, leading to their variety of pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%